PEMBUKTIAN LASER DIODA SPEKTRUM BIRU 1500 miliWatt DIGUNAKAN SEBAGAI KOMPONEN PEMANCAR CAHAYA PADA OPTICAL WIRELESS TRANSFER ENERGY - Wijaya Widjanarka Natasaputra; Wahyu Priyoatmoko; Kapti . (STMIK BINA PATRIA, 2022)
So far, the transfer of electric power is done by wire or cable. Recent discoveries use electromagnetic waves or magnetic induction. In this study, we tried the latest innovations, namely trials to prove with light as a substitute for wire media. The light (beam) used is a laser beam. The use of a diode type laser optical component with a blue color in the technology for wireless transfer of electrical energy. Laser tested 1500 milliWatt power. The working voltage is 6 Volts, 1 ampere. While the measurement of voltage, current and light strength with a multimeter fluxmeter. The electrical load used for this experiment is a red LED (Light Emiting Diode), with an additional 220 ohm resistor, 0.5 watts.This research method uses the type of experiment (experiment).The variables tested and measured are voltage in volts, current in amperes and light intensity in lux. The power supply can be varied from 0 volts to 15 volts, the current is 1.5 amperes of direct current. Light measuring instrument (fluxmeter or lightmeter) is expressed in lux.The results of the tests and measurements are expressed in the form of a graph of the current voltage and light intensity in the form of a graph. At a distance of 3 meters with a source voltage of 6 volts and 1 ampere on the laser, the electrical energy generated is transferred is an electric voltage of 3.9 volts, an electric current of 8.75 milli-Amperes.From this experiment, it can be proven that light can be used as a medium to distribute or transfer electrical energy, from one place to another, which is called optical wireless energy transfer. The transfer of electric power can be done with light.Keywords: Optical Wireless Energy Transfer, Blue Laser-Diode, Lux.